Political survivors : the resistance, the Cold War, and the fight against concentration camps after 1945 - Kuby, Emma, 1981- (Cornell University Press, 2019)
"History of concentration camp survivors who launched an international campaign to expose ongoing crimes against humanity in the 1950s that illuminates how the memory of Nazi atrocity both spurred and distorted Europeans' efforts to comprehend the persistent violence of the Cold War world"--